2008
DOI: 10.1136/adc.2006.105528
|View full text |Cite
|
Sign up to set email alerts
|

Named/designated doctor status and judgement in child-protection scenarios

Abstract: Four child-protection scenarios were sent to 200 named/designated and non-named/non-designated doctors. The respondents judged each scenario as abuse or accident and indicated their degree of certainty. There was a 71% response rate. There were no significant differences in judgement or degrees of certainty of judgement between the two groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Studies of the specialist safeguarding children nurse role have focused on child protection supervision and support (Crisp and Lister, ; Rowse, ) and their role in primary care reforms (Appleton, ). The implementation of the Named Doctor role in a local context has been described by Polnay and Curnock (); they were also the subject of a research study reported by Power (), who used vignettes of a child protection scenario to compare the clinical judgements of specialist and non‐specialist staff. More recently, a survey conducted by the Royal College of Paediatrics and Child Health (, pp.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of the specialist safeguarding children nurse role have focused on child protection supervision and support (Crisp and Lister, ; Rowse, ) and their role in primary care reforms (Appleton, ). The implementation of the Named Doctor role in a local context has been described by Polnay and Curnock (); they were also the subject of a research study reported by Power (), who used vignettes of a child protection scenario to compare the clinical judgements of specialist and non‐specialist staff. More recently, a survey conducted by the Royal College of Paediatrics and Child Health (, pp.…”
Section: Introductionmentioning
confidence: 99%